Maximizing Haematococcus biorefineries: Ionic liquid-based astaxanthin recovery, biocosmetic formulation, solar cell applications, and biofertilizer valorization - Mussagy, Cassamo U.; Caicedo-Paz, Angie V.; Figueroa, Debora; Santander, Christian; González, Felipe; Tropea, Alessia; Mondello, Luigi; Spadaro, Donatella; Trocino, Stefano; Piazza, Rodolfo D. [UNESP]; Marques, Rodrigo F.C. [UNESP]; Godoy, Karina; et al. (Elsevier, 2025)
Microalgae, particularly Haematococcus pluvialis, produce astaxanthin (AXT), a potent antioxidant with growing potential in the food, pharmaceutical, biocosmetic, and renewable energy sectors. This study proposes an integrated biorefinery model that employs advanced extraction processes, including bio-based ionic liquids, to efficiently recover AXT from H. pluvialis while minimizing environmental impact. The resulting platform strategically repurposes the post-extraction biomass as a biofertilizer, thus contributing to zero-waste objectives. By uniting biocosmetics, solar energy applications, and agriculture within a single framework, this model underscores the synergy between economic feasibility and ecological responsibility, highlighting the transformative role of microbial-derived AXT in sustainable, high-value product development.
Keywords: Bioprocessing integration; Haematococcus pluvialis; Microalgae; Neoteric solvents